Correlation between Energy Adequacy Level and Exercise Habits with Nutritional Status in Female Students at al - Hikmah Semarang Islamic Boarding School - Sabilla, Fauza Amanda (Jurnal Gizi dan Kuliner (Journal of Nutrition and Culinary), 2024)
Lifestyle changes in young adulthood affect eating patterns, which will also impact energy adequacy and exercise habits. The opportunity to become overweight is very likely to occur in individuals who have excessive energy levels with poor exercise habits. Research related to the level of energy adequacy and exercise habits with nutritional status is important to know within the scope of Islamic boarding schools so that students can have optimal levels of nutrition and health. The aim of this research is to determine the relationship between the level of energy adequacy and exercise habits with the nutritional status of female students at PPM al - Hikmah Semarang. The method used in this research is a quantitative method with a cross sectional research design. The sample was determined using a total sampling method with a total of 73 respondents. The data measured were the level of energy adequacy and exercise habits using a questionnaire, and nutritional status from BMI. The statistical analysis used is the Chi Square test, Mann - Whitney test, and Kruskal Wallis test. The results of this study showed that the majority of respondents had sufficient levels of energy adequacy (47.9%), poor exercise habits (80.8%), and normal nutritional status (45.2%). There is a significant relationship between the level of energy adequacy and nutritional status with value (p = > 0.001). There was no significant relationship between exercise habits and nutritional status (p = 0.317). The conclusion that can be drawn is that there is a significant relationship between the level of energy adequacy and nutritional status, and there is no significant relationship between exercise habits and nutritional status.